Skin Directed Therapy in Cutaneous T-Cell Lymphoma - Tarabadkar, Erica S.; Shinohara, Michi M. (Frontiers in Oncology, 2019)
Skin directed therapies serve important roles in the treatment of early stage cutaneous T-cell lymphoma (CTCL)/mycosis fungoides (MF), as well as managing symptoms and improving quality of life of all stages. There are now numerous options for topical therapies that demonstrate high response rates, particularly in early/limited MF. Phototherapy retains an important role in treating MF, with increasing data supporting efficacy and long-term safety of both UVB and PUVA as well as some newer/targeted methodologies. Radiation therapy, including localized radiation and total skin electron beam therapy, continues as a cornerstone of therapy for all stages of MF.